Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Okay, this is the last limit I have to solve but it's not that easy ;)

$$\lim_{x\to \infty} (x+3)^{1 + 1/x} - x^{1 + 1/(x+3)}$$

share|improve this question
2  
Actually, it is pretty easy: when $x$ goes to $\infty$, $1/x$ and $1/(x+3)$ go to $0$. Then you're left with $(x+3)^1 - x^1 = 3$. The only (slightly) tricky part is showing that this reasoning is actually sound. –  Ilmari Karonen Aug 28 '11 at 16:06
4  
Yeah, i did the smae but the reasoning is not sounding really legit :D –  Radoslav Georgiev Aug 28 '11 at 16:14
    
With these limit questions why not try out some actual values to get a sense of what's happening? –  Mark Bennet Aug 28 '11 at 16:48
    
@Didier Piau: That's why I said it's a bit tricky. One essentially needs to show that $1/x$ goes to $0$ "fast enough" that $(x+c)^{1+1/x}$ approaches the asymptote $x+c$ as $x \to \infty$. (And how did your comment end up below my reply...?) –  Ilmari Karonen Aug 28 '11 at 16:51
4  
@Ilmari, actually your "indication" is absolutely unsound (and I find most welcome Radoslav's instinctive scepticism here). You could try to test the example $x^{1+1/\log(x)}−x$. You would probably predict that the limit is $0$, and this would be wrong. –  Did Aug 28 '11 at 16:51
show 4 more comments

4 Answers

up vote 13 down vote accepted

One needs to be careful because this is a difference of two functions and each of them converges to infinity, hence the behaviour of their difference can be almost anything.

Write the function of interest as $f(x)=xx^{1/x}g(x)$ with $$ g(x)=(1+3/x)^{1+1/x}-x^{1/(x+3)-1/x}=\mathrm{e}^{a(x)}-\mathrm{e}^{b(x)}, $$ with $$ a(x)=(1+1/x)\log(1+3/x)=3/x+o(1/x), $$ and $$ b(x)=-\frac{3\log(x)}{x(x+3)}=o(1/x). $$ This yields $\mathrm{e}^{a(x)}=1+3/x+o(1/x)$ and $\mathrm{e}^{b(x)}=1+o(1/x)$ hence $g(x)=3/x+o(1/x)$.

Likewise $x^{1/x}=\mathrm{e}^{\log(x)/x}=1+o(1)$ hence $$ f(x)=xx^{1/x}g(x)=x(1+o(1))(3/x+o(1/x))=3+o(1). $$ That is, $f$ does converge and its limit is $3$.

share|improve this answer
1  
Wow :) Thanks for the solution, looks great. –  Radoslav Georgiev Aug 29 '11 at 0:11
    
@Radoslav, you are welcome. –  Did Sep 1 '11 at 22:15
add comment

For constants a, b, consider the asymptotics of $(x+a)^{1+1/(x+b)}$ as $x\to\infty$. This is equal to $(x+a)e^{\log(x+a)/(x+b)}$.

Now since $\log(x+a)/(x+b)$ tends to 0, we know that $e^{\log(x+a)/(x+b)}=1+\log(x+a)/(x+b)+\ldots$ where the $\ldots$ term tends to 0 faster than $\log(x+a)^2/(x+b)^2$.

Then $(x+a)^{1+1/(x+b)}=(x+a)+(x+a)\log(x+a)/(x+b)+(x+a)\ldots$, and since $(x+a)\log(x+a)^2/(x+b)^2$ tends to 0, so does $(x+a)\ldots$.

Therefore $(x+a)^{1+1/(x+b)}-(x+a)-(x+a)\log(x+a)/(x+b)\to0$ as $x\to\infty$.

Note that $(x+a)\log(x+a)/(x+b)-\log(x+a)=(a-b)\log(x+a)/(x+b)\to0$ as $x\to\infty$.

Note also that $\log(x+a)-\log x=\log(1+a/x)\to\log 1=0$ as $x\to\infty$.

Adding these three limits together shows that $(x+a)^{1+1/(x+b)}-(x+a)-\log x\to 0$, which we can rewrite as $(x+a)^{1+1/(x+b)}-(x+\log x)\to a$.

Applying with $a=3$ and $b=0$ gives that $(x+3)^{1+1/x}-(x+\log x)\to 3$. Applying with $a=0$ and $b=3$ gives that $x^{1+1/(x+3)}-(x+\log x)\to 0$.

Subtracting one from the other gives $(x+3)^{1+1/x}-x^{1+1/(x+3)}\to 3$.

share|improve this answer
add comment

$(x+3)e^{((\ln(x+3))/x)}-xe^{((\ln x)/(x+3))}= 3+{(((x+3)\ln(x+3))/x)-((x\ln x)/(x+3))}+o(1)= 3+o(1)$, where the first equality is obtained by Maclaurin series of the exponential function and the last equality is obtained by the trick $\ln(x+3)= \ln x+\ln(1+(3/x))$.

share|improve this answer
add comment

I know the following method is not valid for the purpose of this exercise, but I would like to post it. I computed in the Computer Algebra System included in SWP the following power series expansions:

$$\begin{eqnarray*} (t^{-1}+3)^{1+t} &=&t^{-1}+\left( 3-\ln t\right) +\left( -\frac{3}{2}+\frac{1 }{2}\left( 3-\ln t\right) ^{2}\right) t+O\left( t^{2}\right) \\ t^{-1-1/(t^{-1}+3)} &=&t^{-1}+\left( -\ln t\right) +\left( 3\ln t+\frac{1}{2} \ln ^{2}t\right) t+O\left( t^{2}\right) \end{eqnarray*}$$

and

$$(t^{-1}+3)^{1+t}-t^{-1-1/(t^{-1}+3)}=3+\left( -\frac{3}{2}+\frac{1}{2}\left( 3-\ln t\right) ^{2}-3\ln t-\frac{1}{2}\ln ^{2}t\right) t+O\left( t^{2}\right).$$

Then I generated the asymptotic power series of $(x+3)^{1+1/x}-x^{1+1/(x+3)}$ by the change of variables $x=1/t$

$$\begin{eqnarray*} f(x)&=&(x+3)^{1+1/x}-x^{1+1/(x+3)} \\ &=&3+\left( -\frac{3}{2}+\frac{1}{2}\left( 3-\ln \frac{1}{x}\right) ^{2}-3\ln \frac{1}{x}-\frac{1}{2}\ln ^{2}\frac{1}{x} \right) \frac{1}{x}+O\left( \frac{1}{x^{2}}\right) \\ &=&3+\left( -\frac{3}{2x}+\frac{1}{2x}\left( 3+\ln x\right) ^{2}+\frac{3\ln x }{x}+\frac{\ln ^{2}x}{2x}\right) +O\left( \frac{1}{x^{2}}\right) \\ &=&3+\frac{3}{x}+6\frac{\ln x}{x}+\frac{\ln ^{2}x}{x}+O\left( \frac{1}{x^{2}} \right) \\ &\sim &3, \end{eqnarray*}$$

and confirmed with the following variant $$\begin{eqnarray*} f(x)&=&(x+3)^{1+1/x}-x^{1+1/(x+3)} \\ &=&\frac{\left( x+3\right) ^{1+1/x}x^{-1-1/(x+3)}-1}{x^{-1-1/(x+3)}} \\ &\sim &\frac{1+\frac{3}{x}+\left( -3\ln \frac{1}{x}+3\right) \frac{1}{x^{2}} +O\left( \frac{1}{x^{3}}\right) -1}{\frac{1}{x}+\left( \ln \frac{1}{x} \right) \frac{1}{x^{2}}+O\left( \frac{1}{x^{3}}\right) } \\ &\sim &3\frac{x+\ln x+1}{x-\ln x} \\ &\sim &3. \end{eqnarray*}$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.